2022
DOI: 10.3389/fnmol.2022.815695
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Function of a SINE-VNTR-Alu Retrotransposon to Modulate Isoform Expression at the MAPT Locus

Abstract: SINE-VNTR-Alu retrotransposons represent one class of transposable elements which contribute to the regulation and evolution of the primate genome and have the potential to be involved in genetic instability and disease progression. However, these polymorphic elements have not been extensively analysed when addressing the missing heritability of neurodegenerative diseases, including Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS). SVA_67, a retrotransposon insertion polymorphism, is located in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…In our previous studies, we characterised the impact of SVA RIPs using transcriptomic, whole genome sequencing and clinical data from the Parkinson's Progression Markers Initiative (PPMI) cohort highlighting the association of seven RIPs with the progression of PD and with differential gene expression 32 . Moreover, our recent study also showed the association of the presence or absence of a particular SVA RIP, termed SVA_67, with differential isoform expression of several genes within the MAPT locus 33 . SVA_67, located about 12 kb upstream of the KAT8 regulatory NSL complex subunit 1 (KANSL1) gene, represents a 5´ truncated SVA element with a length of 701 bp (hg38) and tags H1 while its absence is associated with H2 32,33 (Fig.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…In our previous studies, we characterised the impact of SVA RIPs using transcriptomic, whole genome sequencing and clinical data from the Parkinson's Progression Markers Initiative (PPMI) cohort highlighting the association of seven RIPs with the progression of PD and with differential gene expression 32 . Moreover, our recent study also showed the association of the presence or absence of a particular SVA RIP, termed SVA_67, with differential isoform expression of several genes within the MAPT locus 33 . SVA_67, located about 12 kb upstream of the KAT8 regulatory NSL complex subunit 1 (KANSL1) gene, represents a 5´ truncated SVA element with a length of 701 bp (hg38) and tags H1 while its absence is associated with H2 32,33 (Fig.…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, our recent study also showed the association of the presence or absence of a particular SVA RIP, termed SVA_67, with differential isoform expression of several genes within the MAPT locus 33 . SVA_67, located about 12 kb upstream of the KAT8 regulatory NSL complex subunit 1 (KANSL1) gene, represents a 5´ truncated SVA element with a length of 701 bp (hg38) and tags H1 while its absence is associated with H2 32,33 (Fig. 1).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations